Dinamika Negara Hukum dalam Sistem Demokrasi Pancasila di Indonesia - Indra Muchlis Adnan; Muannif Ridwan; Vivi Arfiani Siregar; Mubarik (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research discusses the dynamics of the rule of law in the Pancasila democracy system in Indonesia. This study uses a descriptive qualitative method by presenting various opinions of figures from credible library data. The focus of discussion in this research is related to the dimensions of the rule of law, politics and power which presents political parties and action theory in politic, and the concept of shifting power from a juridical point of view, then politics and power distribution discusses the distribution of power in the Constitution. 1945, the power of the presidential institution, the president and ministers, the power of the Supreme Court (MA), the power of the constitutional court (MK), the power of the Supreme Advisory Council (DPA), and the power of the regional representative council (DPD) and the power of the Supreme Audit Agency (BPK), and also discussed the political dynamics of the past; old order, new order and reform era. At pthe principle of a rule of law is to realize the protection of life for the people against government actions and the recognition and protection of human rights. Because the rule of law concept is rechtstaats, the rule of law, and the constitutional state of Pancasila. Meanwhile, there are three elements of constitutional government; government that is carried out by the public interest, government is carried out according to law based on general provisions, and constitutional government, that is, government that is carried out by the will of the people, not in the form of pressure imposed by the government.